PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVBSD NEGERI 29 PEKANBARU - Fadliansyah, Fadliansyah; Antosa, Zariul; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by low student learning outcomes. This can be seen from 34 students, only 14 students completed with an average of 65,76 while the KKM established by the school is 75. The low learning outcomes of social science students due, teachers who still use lecture and question and answer methods without using media and teachers less apply learning models or teaching strategies that vary in social science learning. The purpose of this study is to improve the learning outcomes of social science students grade IVB SD Negeri 29 Pekanbaru by applying cooperative learning model type examples non examples. This study is a classroom action research, consisting of two cycles. Each cycle consists of two meetings and one daily test at the end of each cycle. The subjects of this study are students of grade IVB SD Negeri 29 Pekanbaru which amounted to 34 students, consisting of 23 male students and 11 female students. This study was conducted in the even semester of the academic year 2016/2017. After the process of improving learning by using cooperative learning model type examples non examples teacher activity in the first cycle increased from 66,66% with enough category, to 79,16% with good category. Then on the second cycle increased again from 87,50% with very good category, to 91,67% with very good category. While the activity of students in the first cycle increased from 62.50% with enough category, to 70.83% with enough category. Then increase again in cycle II from 79,16% with good category, become 87,50% with very good category. Student learning outcomes increased from 65,76 to 73,97 in daily repeat I with a 12,48% increase in percentage and in daily test II increased again to 82,50 with an increase percentage of 24,45%.Keywords: Examples Non Examples, Learning Results Of Social Science